ANALYSIS OF THE LEVEL OF READINESS FOR THE APPLICATION OF ONE VILLAGE ONE PRODUCT IN THE SMALL AND MEDIUM BATIK TULIS INDUSTRY IN SIDOARJO DISTRICT - Tjahjani, Ida Kusnawati; Hakim, Abdul; Yanuwiadi, Bagyo; Satria, Dias (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
This study aims to determine the level of readiness of the Batik Tulis Small and Medium Industry in Sidoarjo district in implementing One Village One Product (OVOP) by mapping the assessment criteria based on the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, as a first step in conducting analysis using the Strengths, Weakness, Opportunities, and Threats (SWOT) method. OVOP is a way to develop the potential of an area that was pioneered by Dr. Morihiko Hiramatsu has succeeded in alleviating poverty in Japan's Oita Prefecture through the Japan External Trade Organization (JETRO) by motivating the economies of several developing countries albeit under different names. Base on the identification of the performance of 30 small and medium industries (SMI) spread across 5 batik centers, it can be seen that the level of readiness is 81%. The results of the 82 evaluation criteria means that the product quality is good and has been classified as 4 star even though the marketing area is only in the country. So that the value still needs to be increased on several indicators (A). Aspects of Production, Product and Community Development, (B). Marketing Aspects and Product History, (C). Aspects of Product Type, Quality, and Market Opportunities. Of the 25 indicators of OVOP product assessment for the batik category, when mapped in the IFE matrix, 8 are seen as strengths and 4 of weakness, while in the EFE matrix, 7 of opportunity and 6 of threats are seen.